2014
DOI: 10.1063/1.4874158
|View full text |Cite
|
Sign up to set email alerts
|

The metallization and superconductivity of dense hydrogen sulfide

Abstract: Hydrogen sulfide (H2S) is a prototype molecular system and a sister molecule of water (H2O). The phase diagram of solid H2S at high pressures remains largely unexplored arising from the challenges in dealing with the pressure-induced weakening of S-H bond and larger atomic core difference between H and S. Metallization is yet achieved for H2O, but it was observed for H2S above 96 GPa. However, the metallic structure of H2S remains elusive, greatly impeding the understanding of its metallicity and the potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
532
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 701 publications
(577 citation statements)
references
References 45 publications
43
532
1
1
Order By: Relevance
“…The superconductivity of a large number of elements and compounds including cuprates [633,634], fullerides [635], intermetallic boron carbides [636], layered nitrides [637], magnesium diboride [638], iron pnictides [639], and recently hydrides [640,641], can be strongly altered and tuned by pressure [642,643]. Many elements, although not superconducting at ambient pressure, become superconductors at HP.…”
Section: Superconductorsmentioning
confidence: 99%
“…The superconductivity of a large number of elements and compounds including cuprates [633,634], fullerides [635], intermetallic boron carbides [636], layered nitrides [637], magnesium diboride [638], iron pnictides [639], and recently hydrides [640,641], can be strongly altered and tuned by pressure [642,643]. Many elements, although not superconducting at ambient pressure, become superconductors at HP.…”
Section: Superconductorsmentioning
confidence: 99%
“…Recent theoretical work 4 indicated that such dissociation would not occur and predicted that H 2 S pressurized at 1.6 million atmospheres would show superconductivity at temperatures above 80 K. This led to the practical work of Drozdov et al, 1 who found that H 2 S compressed in a diamond anvil cell exhibited two astonishing superconductive states at pressures above 1 million atmospheres: the superconductivity ranging from 30 to 150 K measured in the lowtemperature runs (Fig. 1) 1 relates to H 2 S, as it is consistent with calculations; 4 the highest superconductivity of 203 K was achieved in samples annealed at the room temperature (Fig.…”
Section: Yanming Mamentioning
confidence: 99%
“…A DFT study by Li et al 15 was the first to suggest that metallic H 2 S could become a high-temperature superconductor, which they predicted to have a T c of 80 K at 160 GPa. In the same study Li et al 15 also showed that pressure-induced decomposition of H 2 S into its elements was thermodynamically unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…A DFT study by Li et al 15 was the first to suggest that metallic H 2 S could become a high-temperature superconductor, which they predicted to have a T c of 80 K at 160 GPa. In the same study Li et al 15 also showed that pressure-induced decomposition of H 2 S into its elements was thermodynamically unfavorable. This result overturned the conclusion from a DFT study 28 that pressure-induced decomposition into the elements might occur, and suggested that new H/S compounds could be formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation